Neuropathic pain and itch: mechanisms in allergic conjunctivitis. Issue 5 (27th October 2022) - Kalangara, Jerry P.; Vanijcharoenkarn, Kristine; Chisolm, Sarah; Kuruvilla, Merin E.
Abstract : Purpose of review: Allergic conjunctivitis is highly prevalent and affects up to one third of the general population. The current understanding of the pathophysiology and therapeutic strategies center around the type 2 inflammatory pathway. However, there is an increasing body of evidence that suggests neurogenic mechanisms also play a role in allergic inflammation, with a substantial proportion of allergic conjunctivitis patients experiencing both ocular itch and pain. Recent findings: Unmyelinated C fibres on the ocular surface transmit histaminergic itch and can be directly activated by mast cell mediators. The conjunctival mucosa also contains TRPV1+ (histamine-dependent) and TRPA1+ (histamine-independent) neurons that enhance ocular pain and itch in allergic conjunctivitis. Allergen-complexed IgE also binds directly to FcεRI expressed on peripheral neurons. Environmental aeroallergens can also directly stimulate neuronal nociceptors to release inflammatory substances. Allergic inflammation thus stimulates nerve terminals to release vasoactive and inflammatory neuropeptides, leading to a cyclical neuronal dysregulation that augments mast cell activity. These repetitive cycles lead to both peripheral and central sensitization and neuronal plasticity, resulting in decreased itch/pain thresholds and a heightened itch/pain response. Summary: Neurogenic mechanisms including peripheral and central sensitization may drive chronic ocular itch and pain secondary to allergic inflammation. Research into these pathways may help to identify therapeutic targets in allergic conjunctivitis patients with refractory symptoms.